Effect of Deviation from Stoichiometry on Thermal Conductivity of Bi2Se3 Polycrystals - Menshikova, S. I.; Rogacheva, E. I. (Institute of Thermoelectricity National Academy of Sciences of Ukraine, 2020)
The dependences of electronic and lattice thermal conductivity on the composition (59.9 - 60.0) at. % Se of Bi2Se3 polycrystals subjected to a long-term annealing at 650 K. A non-monotonic behavior of these concentration dependences, associated with a change in the phase composition and defect structure under the deviation from stoichiometry, was observed. The boundaries of the Bi2Se3 homogeneity region were estimated. The results of the present work confirm those obtained earlier in our study of the effect of deviation from stoichiometry (59.9 - 60.0 at.% Se) on the electrical conductivity, Hall coefficient, Seebeck coefficient and microhardness of Bi2Se3polycrystals after a similar preparation technology.

Залежності електронної і граткової теплопровідності від складу (59,9 - 60,0) ат. % Se полікристалів Bi2Se3, підданих довготривалому відпалу при 650 К. Спостерігається немонотонність цих концентраційних залежностей, пов’язана зі зміною фазового складу та структури дефектів при відхиленні від стехіометрії. Оцінено межі області однорідності Bi2Se3. Результати даної роботи підтверджують отримані раніше в нашому дослідженні впливу відхилення від стехіометрії (59,9 - 60,0 ат.% Se) на електропровідність, коефіцієнт Холла, коефіцієнт Зеєбека та мікротвердість полікристалів Bi2Se3 після аналогічної технології отримання.
Keywords: bismuth selenide; stoichiometry; concentration; defect structure; thermal conductivity; селенід вісмуту; стехіометрія; концентрація; дефектна структура; теплопровідність